Defense Law as the Foundation of the State Defense System in the Republic of Poland - Kamiński, Mariusz Antoni (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2020)
The article presents an analysis of defense law in the legal system of the Republic of Poland in the context of its importance for the defense of the state. The author discusses the role of the state defense system in ensuring national security and presents defense law as a foundation for effective organization of this system. Moreover, the author analyzes the subject matter of defense law and points out the difficulties in its proper organization. The key issues discussed in the article are the need for defense law reforms and indication of the proposals as to the direction in which changes in this field of law should go.